Neonatal mortality and associated factors at a provincial hospital, Western Province of Rwanda: A facility based cross-sectional study, 2019-2021 - Christophe Nkundabaza; Gilbert Rukundo; Jean d’Amour Sinayobye; Joseph Ntaganira; Judith Mukamurigo (Journal of Interventional Epidemiology and Public Health)
Introduction: Despite progress made towards United Nations SDG targets, neonatal mortality remains a significant challenge in Rwanda, especially in rural areas with a higher mortality rate (20 per 1000 live births) compared to urban regions (15 per 1000 live births). Bushenge Hospital, a rural facility, receives numerous neonatal admissions, yet understanding of neonatal mortality and its determinants is limited. This study aimed to assess the prevalence and factors associated with neonatal mortality at Bushenge hospital.